Suara Perempuan Dalam Narasi Stunting: Systematic Literature Review Berbasis Analisis Gender - Hutaminingsih, Ika (Sociology Department, Brawijaya University, 2026)
Stunting is one of the health problems in Indonesia and is not only related to nutrition. Various studies show that family relationships, especially gender inequality, have a significant influence on women's ability to care for their children's health. This study aims to present women's voices in the narrative of stunting through a Systematic Literature Review (SLR) analyzed using R. W. Connell's Gender and Power theory. This study analyzed 17 articles that met the PRISMA criteria, which were analyzed thematically to understand gender dynamics in families, ranging from gender-based division of labor, gender-based division of power, and cathexis that shapes women's everyday experiences of stunting. The results of the study show that gender inequality between women and men in the family plays an important role in the risk of stunting. Women are responsible for the entire domestic burden and child care, while men tend to occupy the position of primary decision-makers regarding health and the allocation of family resources. Women's limited autonomy in determining family spending and children's nutritional needs has an impact on the quality of care received by children. Women experience a paradox in their efforts to break free from shackles so that they have autonomy, but on the other hand, children are at risk of stunting because they do not receive care from women. In addition, women's acceptance of family responsibilities has an emotional context that perpetuates unequal relations between women and men in the family. There is power in the relationships built between women and men in the family, which is perpetuated by tradition and norms. Interventions must not only increase women's capacity but also involve men in strengthening women's autonomy, which limits women's roles and agency. Presenting women's experiences as the center of analysis contributes to a comprehensive understanding of stunting from a socio-cultural perspective, not just a health perspective.